Dark sons - Grimes, Nikki (Blink, 2010)
Alternating poems compare and contrast the conflicted feelings of Ishmael, son of the Biblical patriarch Abraham, and Sam, a teenager in New York City, as they try to come to terms with being abandoned by their fathers and with the love they feel for their younger stepbrothers.